New Testament interpretation and methods a Sheffield reader - Evans, Craig A.; Porter, Stanley E. 1956- (Sheffield, UK Sheffield Academic, 1997)
Includes bibliographical references and indexes
Articles originally published in Journal for the study of the New Testament
Keywords: Bible. N.T. -- criticism, interpretation, etc